Newsletter No. 27 - (:unkn) unknown (My University, 2010)
Contains news on the progress of Wave 4 and changes to data collection; the NAPLAN data linkage; the 11th Australian Institute of Family Studies Conference and associated data user training; information about accessing Wave 3 data; and updates on Wave 3.5, Wave 5 and beyond, Life at 5 and the ongoing linkage of Medicare data.
27
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology